L'Amérique Méridionale: The Map That Shaped Brazil in the 18th Century - Furtado, Junia Ferreira (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This book explores how the origins of Brazil's modern borders can be traced to the cartography of the Americas produced by the eighteenth-century French cartographer J.B.B. d'Anville. It argues that this map reflects the geopolitical policies of the Portuguese diplomat D. Luis da Cunha, who was involved in Portugal's negotiations with the Spanish to formally establish Brazil's frontiers, and highlights how and why these policies were adopted in the Treaty of Madrid in 1750.